Pengaruh Komunikasi Kerja Dan Stres Kerja Terhadap Kinerja Pegawai Pada Kantor Kecamatan Pondok Aren Kota Tangerang Selatan - Siti Faradilla Rahma; Sri Mulyani (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
performance at the Pondok Aren District Office. The research method used is quantitative with a causal associative approach. Data were collected through questionnaires distributed to employees and analyzed using partial (t-test) and simultaneous (F-test) regression analyses. The results showed that work communication has a significant effect on employee performance, with a t-value of 9.288 > 1.670 and a significance value of 0.000 < 0.05. This means that effective work communication between superiors and subordinates, as well as among colleagues, can improve employee performance. Good communication minimizes misunderstandings, strengthens coordination, and increases motivation to achieve organizational goals. Furthermore, job stress also has a significant effect on employee performance, as indicated by a t-value of 2.248 > 1.670 and a significance value of 0.027 < 0.05. High levels of job stress tend to reduce performance, while controlled stress levels can encourage better work outcomes. Therefore, managing job stress through proper workload distribution, comfortable work environments, and psychological support is essential. Simultaneously, the F- test results show that work communication and job stress together have a significant effect on employee performance, with an F-value of 47.631 > 3.15 and a significance value of 0.000 < 0.05. These findings indicate that effective communication combined with good stress management can create a productive and harmonious work environment that enhances employee performance.